Early Detection of Hypertension in Village Communities Through Routine Examinations and Health Counseling - Huan Frian Pusung; Dion Kunto Adi Patria (KHD Production, 2026)
Hypertension is a major risk factor for cardiovascular disease and is often undetected because it frequently presents without symptoms. Community-based screening and health education through integrated health service posts play an important role in the early detection and prevention of hypertension-related complications. This study aimed to assess blood pressure status and evaluate early hypertension detection practices among community members. A cross-sectional study was conducted involving 58 participants selected using a total sampling technique. Blood pressure was measured with a sphygmomanometer, and early detection practices were assessed using a structured questionnaire. Data were analyzed using univariate analysis to describe the distribution of blood pressure categories and levels of early detection practices. The results showed that 37.9% of respondents were classified as having Stage I hypertension, 27.6% had Stage II hypertension, and 34.5% had normal blood pressure. Regarding early detection practices, 77.6% of respondents demonstrated good practices. Despite generally good early detection practices, a considerable proportion of community members had hypertension. Strengthening routine blood pressure screening and providing continuous health education at the Integrated Health Service posts level are essential to improve hypertension control and prevent complications.